Järnmöllan i Tvååker: Inledning och projektets bakgrund - Magnusson, Gert (Hikuin, 2004)
Järnmöllan in Tvååker. Introduction and background of the project By Gert Magnussen For almost a century the iron mill, Järnmöllan at Tvååker in Halland on the west coast in SW Sweden has been known and discussed. One of the oldest documents about water powered iron production in Europe from 1197, reveals that Järnmöllan was a donation from Absalon, the archbishop of Lund, to the friars of Sorö in Sealand. The discussions have focussed on two main hypotheses: one being that Järnmöllan was a forge, the other that it was a reduction furnace, where the smiths had produced wrought iron out of limonite ore. The interest of the site is due to the fact that the introduction of water power is consideret one of the most important steps towards an increase in iron production and industrialised society. Though the few written documents known from the 13th century was thoroughly analysed, the question of the nature of Järnmöllan remained unsolved. In the 1980s, however, surveys for ancient monuments in the area of Tvååker, revealed some ten sites with ancient slags. From the medieval documents the area of Absalon’s donation could be reconstructed. Within the suggested location one larger site with large slag heaps was found. Could this site be the one mentioned in the medieval documents? If so. would it be possible to shed some new light on the old question about Järnmöllan, the, in written sources, oldest known water powered iron production? In the 1990s a iterdisciplinary research group was set up lead by Hans Andersson, professor in archaeology. The other members were the archaeologists Gert Magnusson, Bo Strömberg and Jens Vellev, the human geographers Per Connelid och Catarina Masher, the historian Rikke Agnete Olsen and the metallurgist Vagn Buchwald. The fieldwork was carried out 1993-95. The source material consisted of four different types: the written document, the remains of furnaces and other constructions in the river valley, the reconstruction of the landscape and the metallurgical analyses. Our intention was that these materials cooperately would lead to a new understanding of the Järnmöllan at Tvååker.